Differences of Onset Menopause between Combined Oral Pills Acceptors with Non Hormonal Acceptors in Jebres District, Surakarta - Rini, Sanda Puspa; Sahir, Endang; Riyadi, Slamet (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: The aim of the present study was to determine the difference of onset menopause between combined oral pills acceptors and non-hormonal acceptors in Jebres District, Surakarta. Combined oral pills contraception causes increased body fat so it can increase the estrogen production by the conversion of androstenedione in peripheral adipose, while non-hormonal contraception (Intra Uterine Device/IUD) does not have such a mechanism, but it may lead to perforation and Pelvic Inflamatory Disease (PID) which can damage womens reproductive organs. Methods: A cross sectional, observational analytic was conducted, in which the sampling technique was two stage cluster random sampling. The sample was 60 postmenopausal women aged 48-59 years old, consisting of 30 women as combined oral pills acceptors and 30 women as non-hormonal acceptors (IUD). This study was conducted in June-July 2014 in Jebres Districts, Surakarta. Data was analyzed by independent t-test by comparing the mean value of onset menopause of the two groups. Results: The results of the independent t-test showed a significant differences between the two groups with p = 0.026, t = 2.290, and 95% CI. The mean value of onset menopause of the combined oral pills acceptors is higher than non-hormonal acceptors (IUD). Conclusions: There are differences of onset menopause were statistically significant between the combined oral pills acceptors and non-hormonal acceptors in Jebres District, Surakarta. Combined oral pills acceptors had a mean onset of menopause is higher than non-hormonal acceptors. Keywords: onset of menopause, contraception, combined oral pills, non hormonal, IUD